Focus groups theory and practice - Stewart, David W. (Applied social research methods series ;, 2007)
Stressing the interaction of the moderator and group as well as the mechanics of designing, conducting and interpreting the outcome of focus groups, this work provides a systematic treatment of focus group interviews within the context of social science research and theory.